Penggunaan Teknik In Sacco Mobile Sebagai Estimasi Kecernaan Nutrien Hijauan Pakan Ternak di dalam Intestinum - Rendi Fathoni Hadi; Kustantinah Kustantinah; Hari Hartadi (Universitas Sebelas Maret (UNS), 2016)
This study aims to explore the potential of forage optimally, the degradation rate of forage nutrients are usually given by the farmers at the time in the intestine of a variety of forage fodder. This study used four kinds of forage feed material: Gliricidia leaves (G), Manilkara leaves (S), Ficus leaves (B) and Cocoa leaves (C). This study was observed in intestinal digestibility. The data taken is nutrient digestibility of rumen and intestinal residues include DM, OM and CP. Samples were incubated in the intestine of cattle that canulation intestine with different time intervals, time/point of incubation: 2, 4, 8, 12, 16, 24, 36 and 48 hours. Samples were incubated in livestock that fistulation intestinal samples of rumen residue. The results showed that the digestibility of nutrients DM, OM and CP respectively forage percentage amount of intestinal digestibility value of feedstuffs in the rumen incubation time of 2-48 hours progressively decreased the percentage of nutrient digestibility. The conclusion of the study when it is time to stay forage in the rumen longer then the more nutrients are degraded by rumen microbes that escapes rumen degradation will be more and more and can be digested in the intestine will be less. Keywords: in sacco mobile, forage, intestine